The dark-red spider mite, Tetranychus ludeni Zacher (Acari: Tetranychidae) – a new pest in Serbian acarofauna - Marić, Ivana; Međo, Irena; Marčić, Dejan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2022)
The dark-red spider mite, Tetranychus ludeni Zacher (Acari: Tetranychidae), is a highly polyphagous species and an important pest of economic plants belonging to the  families Cucurbitaceae, Malvaceae, Fabaceae and Solanaceae, and growing in tropical and subtropical regions. In the Western Palaearctic, its distribution reports have recently come mostly from the Mediterranean Basin, i.e. Portugal, Spain, Italy and Israel. In a survey conducted in Serbia 2019-2021 (comprising 159 sampling locations), T. ludeni was found at 89 locations on 27 plant species of the families Rosaceae (8), Solanaceae (6), Cucurbitaceae (4), Fabaceae (2), Amaranthaceae (2), Asteraceae (2), Apiaceae (1), Convolvulaceae (1) and Poaceae (1). The dark-red spider mite was found in mixed populations with other spider mites (mostly Tetranychus urticae and T. turkestani) in around half of the sampling locations. Heavy infestation and visible symptoms of injury were observed in several locations. Three Rosaceae plant species, plum (Prunus domestica), blackthorn (Prunus spinosa) and crab apple (Malus sylvestris) were its new hosts. Serbian records of T. ludeni from locations situated at latitudes between 42°N and 46°N were the northernmost distribution records of this species in the Western Palaearctic.
Keywords: spider mites; T. ludeni; plant pest; distribution; Serbia